Hawkmoth pollination of the orchid Habenaria clavata: mechanical wing guides, floral scent and electroantennography. (7th November 2019) - Johnson, Steven D; Balducci, Marco G; Shuttleworth, Adam
Abstract: Floral morphology can play a key role in mechanically guiding pollinators towards reproductive structures, particularly when visibility is limited at night, but the functional significance of morphological traits has seldom been considered in this context. Here we describe a remarkably intricate pollination mechanism in the hawkmoth-pollinated African grassland orchid Habenaria clavata, and also document aspects of the reproductive success and chemical ecology of this pollination system. The flowers are pollinated by several short-tongued hawkmoths, particularly Basiothia schenki, which was the most frequent visitor and occurred at all sites. Moths are probably attracted by the strong scent, which was dominated by several oxygenated aromatics that also elicited strong electrophysiological responses from antennae of B. schenki . Apart from the white rostellum lobes and stigma, which serve as a visual guide to the spur entrance, the flower parts are entirely green and indistinguishable from leaves in terms of spectral information. Using motion-activated video cameras we established that the leading edges of the forewings of foraging hawkmoths contact the two upwardly curving petal lobes, and that hawkmoths are then apparently mechanically guided down onto the reproductive structures. Pollinaria are attached in an unusual place – among hairs on the ventral surface of the thorax, between the middle legs – and are brushed over the protruding stigma lobes when the proboscis is fully inserted in the 41-mm-long spur. These results highlight how multiple traits (morphology, spectral reflectance and scent) can act synergistically to ensure transfer of pollen among flowers.